An experimental investigation of foaming in acidic, high FexO slags - Stadler, S.; Eksteen, Jacques; Aldrich, Chris (Elsevier, 2007)
Slag foaming is common in pyrometallurgical processes, such as various non-ferrous operations like sulphide smelting/converting, base metal slag cleaning, steelmaking in basic oxygen furnaces, as well as in electric arc furnaces. Foaming phenomena remains poorly-understood. The purpose of this paper is to analyse the foaming behaviour of SiO2–Al2O3–CaO–Fe2O3–FeO slags upon argon gas injection at various temperatures and slag chemistries, where the slag basicity and FexO were varied. The results are interpreted in terms of physical properties, phase types and phase proportions that were predicted by models from literature. Foaming, as represented by a foam index, appeared to decrease with increasing basicity, until precipitation of solids had occurred. After this point, the foam index increased with increasing basicity. A few published empirical foaming models were statistically evaluated based on the measured foaming indices and physical property predictions, but no conclusive evidence could be found to justify the use of specific predictors of foaming such as bubble size or surface tension depression rather than surface tension.